Research Progress of Solvent-free Lipase Catalysis and Its Application in the Food Field - Jiaying XIN; Qi SONG; Jingyi XU; Weidan ZHANG; Jiao HE; Chungu XIA (Shipin gongye ke-ji)
Lipase is one of the important hydrolase in the food industry, which is widely used in many fields such as production of flavor ester, development of functional ester and the modification of oil and fat. However, the traditional system of lipase-catalyzed reaction requires the use of a large number of organic solvents, if not handled properly, the loss of organic solvents will cause serious pollution to the environment, and the residues of harmful solvent will directly affect the health of consumers and cause food safety incidents. Lipase catalysis in solvent-free system has many advantages, such as no use of toxic and harmful reagents, high safety, fast reaction speed, high conversion and good selectivity, which has attracted great attention from academia and food industry. However, the solvent-free reaction system also has a lot of shortcomings such as the reaction conditions are harsh, some reactions are difficult to carry out, and the poor fluidity of the reaction system leads to the difficulty of diffusion. As a result, researchers have developed a variety of assisted strengthening methods such as mechanical, microwave, and ultrasound to optimize the reaction effect. In this paper, the types of lipase-catalyzed reactions in solvent-free system, the assisted strengthening methods and its applications in the food field are reviewed so as to provide the reference for subsequent research and application.